Analisis Stimulus Respons Video Kekerasan Seksual pada Youtube Akeloy Production terhadap Mahasiswa KPI IAIN Madura - Indana Salsabila Zulfa; Heny Triyaningsih (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study analyzes how the stimulus in the short video “Guru Tugas 2” broadcast by the Youtube channel Akeloy Production, triggers responses from KPI (Islamic Communication and Broadcasting) students at IAIN Madura, particularly in the context of a case especially in the context of the case of sexual violence by the duty teacher against his students. The purpose of this research is to understand how people respond to the stimulus of sexual violence in digital media. The method used is qualitative research with a descriptive approach, relying on primary data from the video and students responses, as well as secondary data from related literature. The results showed that the video elicited a variety of reactions, including outrage, condemnation, and calls to remove the content, arguing that its representation could damage the image of pesantren and the profession of task teachers. The conclusion of this study emphasizes the importance of ethical considerations in the production of digital content, especially in raising sensitive issues such as sexual violence, to avoid negative impacts on certain groups and broader social perceptions.